Analisis Habituasi Sanitasi Sekolah Pasca Covid 19, Adaptasi Kebiasaan Cuci Tangan Pakai Sabun (CTPS) dan Metode 3R (Reduce, Reuse, Recycle) Sampah pada Sekolah Dasar Daerah Perbatasan - Jewarut, Siprianus; Alnija, Marianus Dinata; Sumarni, Margaretha Lidya; Firgia, Listra (LP. Ma'arif Janggan Magetan, 2023)
This study aims to determine the consistency of the implementation of sanitation, especially the habit of washing hands with soap (CTPS) and the 3R (Reduce, Reuse, Recycle) waste management method in elementary schools in border areas. In carrying out the research it was found that the level of understanding of elementary school students in border areas about sanitation was still very low with a percentage reaching 70.00%, this was in line with the practice of implementing sanitation in schools which was still quite low, especially in the practice of washing hands with soap (CTPS) and maintaining cleanliness. waste reached 60.00%. While the results of a questionnaire with teacher respondents showed an understanding level of sanitation reaching 70.00%, this is in line with the practice of maintaining sanitation in the form of Hand Washing with Soap (CTPS) reaching 80.00%, but at the point of waste processing specifically with the 3R method (Reduce , Reuse, Recycle) garbage, 80.00% of respondents' answers did not understand the method. The linearity of the answers from the two respondent subjects on the activity of maintaining sanitation in schools consistently answered that it had not been carried out properly with a percentage of 70.00%. This is then clarified by the results of observations and interviews which show the practice of maintaining sanitation in the form of Hand Washing with Soap (CTPS) processing 3R (Reduce, Reuse, Recycle) waste. In the 3 elementary schools in the border area which were the observation sites, there was consistency with the facts on the ground that the implementation of sanitation in the form of Hand Washing with Soap (CTPS) processing 3R (Reduce, Reuse, Recycle) waste post-Covid 19 had not been carried out.